The Effect of Vitamin C on Ischemia Reperfusion Injury Because of Prolonged Tourniquet Application With Reperfusion Intervals - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2009)
We examined the effect of vitamin Con muscle injury distal to the tourniquet which was applied for 4 hours with 10- and 20-minute reperfusion intervals after 2 hours of tourniquet. Sixty-four Sprague-Dawley rats were allocated to 4 randomized groups. After 2 hours tourniquet, 10- and 20-minutes of reperfusion were allowed to half of each group respectively. Afterward an additional 2 hours compression was applied. Except the control group the animals received vitamin C intravenously, before the first tourniquet in Group 1, at the reperfusion interval in Group 11, and at both times in Group III. Malondialdehyde levels were measured in blood and the tibialis anterior muscle. The muscle was histopathologically examined. The data was evaluated statistically. The effects of timing and the dose of vitamin C on ischemia reperfusion injury remain controversial and there was no statistical difference between 10- and 20-minute reperfusion intervals. But the blood malondialdehyde levels showed that vitamin C has a positive effect on the muscle injury caused by ischemia-reperfusion.
Keywords: ischemia reperfusion injury; tourniquet; vitamin C; SKELETAL-MUSCLE INJURY; COMPARTMENT SYNDROME; ASCORBIC-ACID; CELL-ADHESION; LUNG INJURY; NEUTROPHIL; RELEASE; DISTAL; LIMB